Molecular structure of starch isolated from jackfruit and its relationship with physicochemical properties - Zhang, Yanjun (Sci Rep, 2017)
The molecular structure of starches isolated from five jackfruits (M2, M3, M4, M8 and X1) and its relationship with physicochemical properties were investigated. Although they had uniform amylose (AM) content, the five jackfruit starches displayed different physicochemical properties, including their pasting, thermal, crystal and texture properties. Furthermore, differences in the molecular structure (i.e., average weight-average molar mass (Mw) of amylose and amylopectin (AP) as well as the same AP fine structure) were also found in the five jackfruit starches. The results indicated that jackfruit starch with a larger Mw of amylose and proportions of DP 25–36, DP ≥ 37 and chain length had a lower peak viscosity, breakdown, final viscosity, setback and adhesiveness, but a higher pasting and gelatinization temperature, gelatinization temperature range, gelatinization enthalpy and relative crystallinity. Xiangyinsuo 1 hao (X1) starch, which originated from Xinglong in Hainan province, China, had special physicochemical properties, which were ascribed to its lower amylopectin Mw, smaller particle size, and perfect amylopectin structure. The results showed that the most important intrinsic factors that could determine the physicochemical properties of starch were its molecular structure, including the Mw of amylose and AP as well as a fine AP structure.